1997
DOI: 10.1097/00004424-199710000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Computed Tomography Characterization of Renal Cell Tumors in Correlation with Histopathology

Abstract: Small clear cell tumors often fail to show the CT characteristics that would permit an accurate classification. In tumors measuring 3 cm or more, differentiation between clear cell and nonclear cell types by means of CT criteria is possible. Nevertheless, as RCTs show a great variation in appearance, a differentiation into subtypes of the nonclear cell RCTs cannot be accomplished by CT. Using a uniform examination protocol and spiral scanning technique, the sensitivity of CT in the diagnosis of the subtypes of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
16
0
2

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(22 citation statements)
references
References 23 publications
4
16
0
2
Order By: Relevance
“…The results of this study are like other international studies [14][15][16][17][18][19][20][21]. The study conducted by Bird et al [15] and Young et al [16] also proved that RCC and Oncocytoma can be differentiated on the basis of degree on enhancement at multidetector CT.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The results of this study are like other international studies [14][15][16][17][18][19][20][21]. The study conducted by Bird et al [15] and Young et al [16] also proved that RCC and Oncocytoma can be differentiated on the basis of degree on enhancement at multidetector CT.…”
Section: Discussionsupporting
confidence: 87%
“…The study conducted by Bird et al [15] and Young et al [16] also proved that RCC and Oncocytoma can be differentiated on the basis of degree on enhancement at multidetector CT. However, Zhange et al [19] Wildberger et al [20] and Davidson et al [21] were unable to differentiate RCC from Oncocytoma. This was because Young et al and Bird et al has relatively larger cohort of these tumor and used four phase protocol rather than three phase protocol.…”
Section: Discussionmentioning
confidence: 99%
“…In our institute, most renal parenchymal neoplasms were first suspected by physicians to be RCCs in the process of examinations for non-urological diseases. About 6%-8% of renal tumors were AML, the most common benign lesions [3,5] . The study group contained most of space occupying lesions, both malignant carcinoma and benign tumor, including cysts and renal abscess.…”
Section: Discussionmentioning
confidence: 99%
“…In the published studies, some characteristics such as enhancement pattern, presence or absence of calcification and cystic degeneration, tumor-spreading pattern and vascularity are overlapping among the subtypes of RCC, although a combination of them may help predicting a specific tumor subtype [71][72][73][74][75][76][77][78][79] . The degree of enhancement has been reported to be a unique CT finding for the differentiation of conventional clear cell RCC from nonconventional subtypes [71][72][73] . Jinzaki et al [74] reported that clear cell RCC showed a peak attenuation value in the cortical nephrographic phase of 1 100 HU, whereas for other subtypes the values were !…”
Section: Diagnosis Of Primary Tumormentioning
confidence: 99%